KAJIAN INTERAKSI OBAT ANTIHIPERTENSI PADA PASIEN HEMODIALISIS DI BANGSAL RAWAT INAP RSU PKU MUHAMMADIYAH YOGYAKARTA PERIODE TAHUN 2010 - Siti Rahmiati; Woro Supadmi (Pharmaciana, 2012)
Drug interactions are one of the Drug Related Problems (DRPs) that may affect patient treatment outcomes. Hypertension occurs in approximately 10% to 81.5% of hemodialysis patients. The purpose of this study was to determine the incidence of antihypertensive drug interactions in hemodialysis patients in the inpatient wards PKU Muhammadiyah Hospital of Yogyakarta period in 2010. This study descriptive design. Data retrieved retrospectively. Data retrieval were done by taking all the data that meet the criteria of existing research on the medical records of hemodialysis patients in PKU Muhammadiyah Hospital of Yogyakarta who received antihypertensive with above normal blood pressure (= 130/80 mmHg). Data were analyzed based on the descriptive level of significance, onset, and severity. The results showed that there were 54.79% (40 patients) of 73 hemodialysis patients potentially experienced drug interactions. Antihypertensive drugs most widely used in hemodialysis patients were ACEI, CCB, and diuretics. Incidence of antihypertensive drug interactions 27 cases (45.76% were most common at a significance level 3, 48 cases (81.36%) were onset delayed, and the severity minor of 44 cases (74.58%). The mechanism of interactions pharmacodynamic were 37 cases (62.71%) of the total 59 events that have drug interactions. Drugs often interactions were furosemide and captopril.